M31. THE ASSOCIATION BETWEEN BULLYING VICTIMIZATION AND PSYCHOSIS AND THE MEDIATING ROLE OF PEER AND FAMILY SOCIAL SUPPORT. (18th May 2020) - Shannon, Ciaran; Jordan, Julie-Ann; Higgins, Kathryn; Kelly, Grace; Mulholland, Ciaran
Abstract: Background: The relationship between psychotic symptoms and bullying has received limited attention to date. A systematic review by Cunningham, Hoy, & Shannon (2016) identified only ten studies that met their inclusion criteria for examining the relationship between childhood bullying and psychosis via a prospective research design. A meta-analysis of these studies suggested that being bullied does predict the later development of psychotic symptoms. The authors went on to say that a better understanding of the factors that mediate the bullying/psychosis relationship is needed. It is possible that prolonged exposure to social adversity and exclusion can lead to a state of "social defeat" which has also been found to increase the risk of psychosis (Johnston et al., 2011; Selten et al., 2013; Selten and Cantor-Graae, 2005). Being bullied in childhood has also been linked to depression in adulthood (Bowes et al. 2014), and social support from family and friends may also mediate the bullying victimisation-depression relationship. Methods: The present study is a secondary data analysis of a prospective cohort study; namely, the Belfast Youth Development Study (BYDS). The BYDS followed a group of children longitudinally from ages 12–21 years. The participants are 2, 087 individuals who took part in the Belfast Youth Development Study (BYDS) in 2011 (Wave 7). This longitudinal survey started in 2001 (Wave 1) when the sample members were aged 11 years. The sample were then surveyed again annually up until age 15 years (Waves 2–5), and post-compulsory schooling follow ups were carried out at 17 and 21 years (Waves 6 & 7). The secondary analysis will involve conducting path models. The first of which will be a bullying victimisation-psychosis mediation model; this will include a predictor (bullied, age 12 years), outcome (Psychosis, age 21 years), mediators (e.g. peer attachment, age 13 years; parental attachment. age 14 years), and covariates (gender, free school meals, depression, and frequency of cannabis use in the past year; cannabis abuse screening test). A bullying victimisation-depression mediation model will also be examined; this will include the same mediator and covariate variables. Results: The results will be reported in the poster submission (analysis in progress). These will include measures of direct and indirect effect, as well as model fit statistics. Discussion: Clinical implications in terms of prevention, assessment, and intervention for young people at risk of psychotic disorders will be discussed.